The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10979-007-9097-5
|View full text |Cite
|
Sign up to set email alerts
|

Does interrater (dis)agreement on Psychopathy Checklist scores in sexually violent predator trials suggest partisan allegiance in forensic evaluations?

Abstract: Many studies reveal strong interrater agreement for Hare's Psychopathy Checklist-Revised (PCL-R) when used by trained raters in research contexts. However, no systematic research has examined agreement between PCL-R scores from independent clinicians who are retained by opposing sides in adversarial legal proceedings. We reviewed all 43 sexual-offender civil-commitment trials in one state and identified 23 cases in which opposing evaluators reported PCL-R total scores for the same individual. Differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
181
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(200 citation statements)
references
References 34 publications
(53 reference statements)
16
181
3
Order By: Relevance
“…(e.g., DeMatteo, et al, 2014;Murrie et al, 2008;Murrie, Boccaccini, Turner, Meeks, Woods, & Tussey, 2009) and in Canada (Lloyd, Clark, & Forth, 2010). Beyond these studies, surveys of judges and attorneys consistently reveal their concern about bias among experts as well (e.g., Krafka, Dunn, Johnson, Cecil, & Miletich, 2002;Shuman, Whitaker, & Champagne, 1994).…”
Section: Bias In Forensic Evaluationsmentioning
confidence: 98%
“…(e.g., DeMatteo, et al, 2014;Murrie et al, 2008;Murrie, Boccaccini, Turner, Meeks, Woods, & Tussey, 2009) and in Canada (Lloyd, Clark, & Forth, 2010). Beyond these studies, surveys of judges and attorneys consistently reveal their concern about bias among experts as well (e.g., Krafka, Dunn, Johnson, Cecil, & Miletich, 2002;Shuman, Whitaker, & Champagne, 1994).…”
Section: Bias In Forensic Evaluationsmentioning
confidence: 98%
“…In a research context, misuse of these instruments will have few negative consequences for the person tested. However, when the scores are used in clinical and criminal justice contexts 42 It is important when conducting an assessment to use all information available to provide a complete picture of the person. In each case, the PCL-R must be used properly and in accordance with the highest ethical and professional standards.…”
Section: Pcl-r Assessment Of Psychopathymentioning
confidence: 99%
“…A recent review of rater agreement findings from more than 120 PCL-R studies found that about half provided little or no information concerning whether independent interviews were used for the cases used to check rater agreement (Rufino et al, 2009). In only a handful of studies was it clear that rater agreement statistics were based on cases in which both evaluators conducted an independent interview (see, e.g., Levenson, 2004;Murrie, Boccaccini, Johnson, & Janke, 2008;Rutherford, Cacciola, Alterman, McKay, & Cook, 1999;Tyrer et al, 2005). In several of these studies, ICC values were notably lower than those reported in the PCL-R manual.…”
mentioning
confidence: 99%
“…More recently, Murrie et al (2008) compared rates of agreement between PCL-R scores provided by experts called by opposing sides (termed ''petitioners'' and ''respondents'') in Texas Sexually Violent Predator (SVP) civil commitment cases. In 23 cases, an expert retained by the respondent also administered the PCL-R. For the total score, the single-evaluator ICC 1 for absolute agreement across these cases was .39, well below the high levels of agreement observed for the PCL-R in most research contexts.…”
mentioning
confidence: 99%